Control of Hereditary Elbow Disease in Pedigree Dogs - Bedford, P.G.C. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
One of the major activities of the World Small Veterinary Association over the past 12 months has been the investigation of potential international measures for the control of inherited disease in the pedigree dog. Three areas of concern are currently being examined: elbow dysplasia, hip dysplasia and ocular disease. The standardisation of diagnostic expertise on an international basis is high on the list of priorities for any scheme to prove successful, and with this intent in mind the first joint WSAVA/Kennel Clubs meeting was held in 1993 on the subject of elbow dysplasia. This report of the meeting was accepted as Association policy by the WSAVA Assembly at its annual meeting in October last year. A form of certification is currently being prepared and next a joint meeting to discuss hip dysplasia will take place in June of this year.